Role of Antibody Anti-AGE in the Expression of Nephrin and RAGE on Primary Glomerulus Cell Exposed with AGE - Salam, Rudy; Lyrawati, Diana; Samsu, Nur (Journal of Tropical Life Science, 2017)
Upregulation of nephrin expression occurs at the early stage of nephropathy and decrease in the period 6 months on hyperglycaemic condition. Nephrin is associated with the initial stage of the loss of the permeability barrier in diabetic nephropathy. Interaction AGE-RAGE increases angiotensin II on Renin Angiotensin-Aldosterone System (RAAS) and activation of protein kinase c (PKC) which induce alterations in nephrin mRNA expression. Alterations of nephrin expression induces transformation of slit membrane structure and the permeability changes at the glomerular filtration barrier. Anti-AGE vaccination once may cause the changes of nephrin and RAGE expression and can prevent progression of diabetic nephropathy. This study used primary glomerulus cell culture obtained from renal of Wistar mice aged 3 months, weighting 200-300 grams that consist of negative control group that exposed to BSA 100 µg/ml, positive control group that exposed to AGE-BSA 100 µg/ml, treatment group 1 that exposed to polyclonal anti-AGE 5 µg/ml and AGE-BSA 100 µg/ml and treatment group 2 that exposed to monoclonal antibody anti-CML 5 µg/ml and AGE-BSA 100 µg/ml. Paired t-test with a 0.05 level of confidence results showed that there were significant differences in level of RAGE expression among experimental groups with control groups. Administration of polyclonal antibody decreased RAGE expression among negative control (p=0.188). but not in positive control (p=0.000). In contrast to monoclonal anti-AGE antibody, RAGE expression did not differ significantly compared to negative control but significant than positive control. Administration of monoclonal anti-AGE antibody inhibited increasing of nephrin expression compared to negative and positive control (p=0.73; 0.125). In conclusion, this study suggested that administration of polyclonal and monoclonal anti-AGE antibody could inhibit increasing of RAGE and nephrin expression in glomerulus primary culture that exposed to AGE which is expected to prevent the progression of diabetic nephropaty.